Analisis Pendekatan Mimetik Lagu “Di Udara” Group Band Efek Rumah Kaca - Munir, Misbahul (Jurnal Ilmu Sosial, Humaniora dan Seni, 2024)
This article analyzes the song “In the air" by the band Greenhouse Effect using a mimetic approach. The aim of this research is to find out how song lyrics reflect socio-political realities in Indonesia, especially injustice, freedom of expression, and threats to human rights activists. The mimetic approach here assumes that literary works are imitations or representations of the world and human life. The analysis is carried out by examining how the lyrics of the song "in the air" reflect social phenomena, human emotions or certain views on life. This research found that the lyrics of the song "In the air" reflect the situation of a person's struggle in facing threats, intimidation, and theorism. These texts can also be read as a critique of systems and structures that use threats of violence to silence voices of resistance.